PENGARUH MIKROORGANISME TERHADAP PRODUKTIVITAS ENERGI LISTRIK MFC DENGAN VARIASI LIMBAH PABRIK TAHU DAN LIMBAH PERIKANAN - NOVRIANDY, MUHAMMAD (JTAM ROTARY, 2021)
Energy is a very fundamental necessity in human life. Current energy usage is highly dependent on the surrounding environment. Especially in remote areas, which require simple energy instruments such as batteries or fuel cells. The Fuel cell is an energy instrument that transfers electricity from a rechargeable source using external materials. Microbial Fuel Cell (MFC) is an alternative form of environmentally friendly energy that is commonly used as a source of energy in the future. MFC is an energy instrument that can convert chemical energy into electrical energy through catalytic reactions by utilizing microorganisms. Plant waste tofu and fishery waste is a waste that contains a lot of carbohydrates, proteins, and fats that usually cause heavy pollution to the waters. By utilizing the liquid waste itself is one way of solving problems in the environment and lack of energy by using the MFC system. For the experiment, this time aimed to compare the electrical energy generated between waste plant tofu and sewage fisheries. In a strong MFC experiment current on plant waste knows an increase as much as 1.47% of fisheries waste, while for voltages in the trial MFC waste fisheries have increased by 1.19% from tofu plant waste.